2011
DOI: 10.3998/jmmh.10381607.0006.103
|View full text |Cite
|
Sign up to set email alerts
|

Muslim Chaplain’s Role as Perceived by Directors and Chaplains of New York City Hospitals and Health Care Settings

Abstract: As more hospitals acknowledge the importance of spiritual care, there is an increasing demand for chaplains who can meet patients' spiritual needs. While most empirical studies thus far have focused on changes in chaplaincy services, and on the role of non-Muslim chaplains, very few have addressed the religious diversity among hospital chaplains and their roles in serving a diverse population. This study will be the first to examine the roles Muslim chaplains play in New York City hospitals and health care set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A study conducted among Iranian medical students found that willingness to donate organs was more than two times higher among those who were aware of religious rulings in support of organ donation, indicating the importance of religious rulings on shaping attitudes and behaviors regarding organ donation . In the USA, chaplains (both Muslim and non‐Muslim) and hospital directors (all non‐Muslim) ranked handling directive education and organ donation as one of the most important roles of a Muslim chaplain …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted among Iranian medical students found that willingness to donate organs was more than two times higher among those who were aware of religious rulings in support of organ donation, indicating the importance of religious rulings on shaping attitudes and behaviors regarding organ donation . In the USA, chaplains (both Muslim and non‐Muslim) and hospital directors (all non‐Muslim) ranked handling directive education and organ donation as one of the most important roles of a Muslim chaplain …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the divided opinions of Islamic scholars and Imams have also resulted in some confusion. Knowledge of organ donation and the relevant Islamic rulings, influence of family members and religious leaders, and trust in the medical system are major factors that influence the decision of Muslims to pursue organ donation . A lack of resources and experts to transfer the knowledge to the community may also have an impact…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Research on Muslim chaplains in the USA, for instance, found a low rate of referral of congregants to mental health professionals among chaplains. [25][26][27][28] This indicates the need for increased understanding in order to build better bridges between Muslims and mental health services. The next section thus focuses on Islam, Muslims and mental health.…”
Section: Public and Private Religiositymentioning
confidence: 99%
“…If the individual has neither art nor an object, but an opportunity for a follow-up meeting exists, the spiritual caregiver could encourage the patient or family member to bring to the next meeting something that represents the story or stories being discussed. One potential downside of this approach, however, is that often spiritual caregivers are limited in terms of how often or for how long they can visit with those who wish for, need, or even might benefit from their support (Abu-Ras, 2011; Barry, 2003; CBC News, 2016; Vanderwerker, Handzo, Fogg, & Overvold, 2008).…”
Section: Technique: How To Use Story and Art/objectsmentioning
confidence: 99%